Case report of a suspected pheochromocytoma co-presenting with a glioblastoma multiforme: case report and review of the literature. (2nd January 2020) - Tresman, Rachel; Dubois, Cyril; Lethbridge, Emma; Robson, Victoria Anne; Lennard, Thomas; Ball, Stephen; Surash, Surash
Abstract: The combination of a pheochromocytoma with any brain neoplasm is a rare occurrence, to our knowledge, this is the first reported case of a glioblastoma multiforme co-presenting with undiagnosed pheochromocytoma.